Marital Separation in Poland. Regional Approach - Mieczysław Kowerski; Magdalena Kowal (Barometr Regionalny, 2014)
In the paper the basic regional trends of marital separation which is, especially for Catholics, an alternative institution to divorce in Poland were presented. After a rapid increase at the beginning of the 21st century, the number of ordered separations started to decrease and now the relation of separations to divorces is smaller than 5%. Regionally, it is observed that the differentiation of the intensity of separations among various voivodships is decreasing, yet in more urbanized voivodships, which have a lower religiousness rate and a higher divorce rate, separations are more common.